Individual and environmental contingencies associated with multiple suicide attempts among U.S. military personnel. (30th August 2016) - Bryan, Craig J.; Rudd, M. David; Wertenberger, Evelyn
Abstract: Suicidal behavior among U.S. military personnel persists as a significant public health issue. Previous research indicates the primary motive for suicide attempts among military personnel is the desire to reduce or alleviate emotional distress, a finding that converges with studies in nonmilitary samples. Much less is understood about the consequences of a first suicide attempt that could influence the occurrence of additional suicide attempts. In order to identify these contingencies, 134 active duty Soldiers who had attempted suicide (n=69 first-time attempters, n=65 multiple attempters) participated in structured interviews focused on their experiences immediately following their first attempt. Soldiers were more likely to have made multiple suicide attempts if they were younger at the time of their first attempt, were not admitted to a hospital or treatment program after their first attempt, or experienced emotional and psychological relief immediately afterwards. Results suggest that Soldiers who experience emotional and/or psychological relief immediately after their first suicide attempt or do not receive treatment are more likely to make additional suicide attempts. Highlights: Little is known about factors that may facilitate repeated suicide attempts. Emotional relief after a first attempt was associated with additional attempts. Receiving treatment after a first attempt was associated with decreased risk. Post-suicide attempt experiences could affect risk for further attempts.